Sistem Pakar Penyakit Liver Menggunakan K- Nearest Neighbors Algoritm Berbasis Website - Citra Yustitya Gobel (ILKOM Jurnal Ilmiah, 2018)
The liver is largest organ for humans, functioning as formation and secretion of bile, and as detoxification of toxins. Liver disease difficult to detect at early stage, but treatment of Liver disease in early stages will greatly help patient's recovery. With increasing number Liver Patients other than caused by unhealthy lifestyle, also caused by delay factor handling early symptoms. So this research aims to design Expert System Liver Disease based Website, that it can facilitate access information society need information about liver disease. Website based system design using K-NN Method because it is considered flexible enough and has tolerance to data that is’not appropriate and based on natural language. Expert system as a tool in determining whether the patient was suffering from Liver disease or not with the concept of K-NN. The results discussion that system design with a simple model so that can be used by all community.